The Biochemistry and Molecular Biology of Xenobiotic Polymer Degradation by Microorganisms - KAWAI, Fusako (Bioscience, biotechnology, and biochemistry, 2010)
Research on microbial degradation of xenobiotic polymers has been underway for more than 40 years. It has exploited a new field not only in applied microbiology but also in environmental microbiology, and has greatly contributed to polymer science by initiating the design of biodegradable polymers. Owing to the development of analytical tools and technology, molecular biological and biochemical advances have made it possible to prospect for degrading microorganisms in the environment and to determine the mechanisms involved in biodegradation when xenobiotic polymers are introduced into the environment and are exposed to microbial attack. In this review, the molecular biological and biochemical aspects of the microbial degradation of xenobiotic polymers are summarized, and possible applications of potent microorganisms, enzymes, and genes in environmental biotechnology are suggested.